Social Statistics in Nigeria 1980 - Federal Office of Statistics (Lagos, Nigeria : Director of Statistics, 1980)
The social statistics report is a compendium of social statistics for the country portraying the contemporary social situation.
rua 16/02/15
Loans
Keywords: Nigeria -- social conditions -- statistics; Nigeria -- Federal Office of Statistics